Tribological study of modified palm oil-with single and hybrid nanofluids for metalworking fluid - Sabri, Ainaa Mardhiah; Talib, Norfazillah; Abdul Sani, Amiril Sahab; Abdullah, Haslina; Kamdani, Kamaruddin (2023)
Metalworking fluids (MWFs) are essential for minimizing wear and fric-tion during machining operations. Vegetable oils have excellent lubricating proper-ties, are highly biodegradable and nontoxic, and are very affordable to manufacture, making them a great replacement for mineral oil as a metalworking fluid. The incorpo-ration of nanoparticles to vegetable oil is a viable strategy to improve the lubricating capabilities of MWFs. The aim of the research is to assess the tribological properties of modified refined, bleached, and deodorized (MRPO) palm oil with 0.025 wt.% of additives. MRPO was produced by transesterification process of refined, bleached and deodorized palm oil (RBD PO). The samples that were tested were MRPO, MRPO with activated carbon (AC) (MRPOa), MRPO with tungsten disulfide (WS2) (MRPOw), and MRPO with a hybrid of AC and WS2 (MRPOaw). The oil samples were then compared with synthetic ester (SE). A four-ball wear test was used to evaluate the tribological performance of oil samples based on ASTM D4172. The testing was done at temperature set to 75 ± 2 °C, load of 392 N, rotating speed of 1200 rpm for 60 min. MRPOaw show the lowest COF (0.06281) and smallest MWSD (607.1 μm). The outcomes of the tribological tests offer insightful information on the performance of these nanofluids, opening the door for their prospective use in efficient and environmentally friendly metalworking procedures